2006
DOI: 10.1016/j.ccr.2006.04.004
|View full text |Cite|
|
Sign up to set email alerts
|

Expression profiling of EWS/FLI identifies NKX2.2 as a critical target gene in Ewing's sarcoma

Abstract: Our understanding of Ewing's sarcoma development mediated by the EWS/FLI fusion protein has been limited by a lack of knowledge regarding the tumor cell of origin. To circumvent this, we analyzed the function of EWS/FLI in Ewing's sarcoma itself. By combining retroviral-mediated RNA interference with reexpression studies, we show that ongoing EWS/FLI expression is required for the tumorigenic phenotype of Ewing's sarcoma. We used this system to define the full complement of EWS/FLI-regulated genes in Ewing's s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
393
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(416 citation statements)
references
References 43 publications
17
393
2
1
Order By: Relevance
“…This experiment further indicates that GLI1 expression in EFT cell lines is dependent on EWS/FLI1 expression. These data agree with findings recently published (in aggregate form) in which RNAi targeting a different region of EWS/FLI1 was used in another Ewing cell line (Smith et al, 2006). In that study, GLI1 was among the genes whose expression was both diminished by EWS/FLI1 RNAi and restored by reexpression of EWS/FLI1.…”
Section: Ews/fli1 Deregulates Gli1supporting
confidence: 93%
“…This experiment further indicates that GLI1 expression in EFT cell lines is dependent on EWS/FLI1 expression. These data agree with findings recently published (in aggregate form) in which RNAi targeting a different region of EWS/FLI1 was used in another Ewing cell line (Smith et al, 2006). In that study, GLI1 was among the genes whose expression was both diminished by EWS/FLI1 RNAi and restored by reexpression of EWS/FLI1.…”
Section: Ews/fli1 Deregulates Gli1supporting
confidence: 93%
“…EWS/FLI requires both its strong transcriptional activation domain (derived from EWS) and its ETS-type DNA-binding domain (derived from FLI) for oncogenic function (May et al, 1993a, b). A variety of studies have identified a large number of EWS/FLI-regulated genes (Prieur et al, 2004;Smith et al, 2006). However, only a handful of these genes have been shown to participate in Ewing's sarcoma oncogenesis.…”
Section: Formationmentioning
confidence: 99%
“…These data sets included (i) the transcriptional profile of EWS/FLI in Ewing's sarcoma cells (produced by comparing patient-derived Ewing's sarcoma cells with retroviral-mediated RNA interference (RNAi) constructs targeting EWS/FLI with those harboring control constructs; Kinsey et al, 2006;Smith et al, 2006), (ii) genome-wide localization data of EWS/ FLI in Ewing's sarcoma cells (produced by 'ChIP-chip' experiments; and (iii) comprehensive mapping data of GGAA-microsatellites in the human genome (produced computationally; . Through these cross-platform comparisons, we identified genes that have all of the characteristics we sought.…”
Section: Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…7 NKX2-2, a homeodomain-containing transcription factor involved in neuronal development and glial/neuroendocrine differentiation, 8,9 is a downstream target of EWSR1-FLI1 oncogenic signaling in Ewing sarcoma. 10 In recent times, NKX2-2 has been reported as a diagnostically useful immunohistochemical marker for Ewing sarcoma. 11 In published studies on NKX2-2 expression in Ewing sarcoma, 11,12 only classic Ewing sarcomas with EWSR1-FLI1 rearrangement have been evaluated.…”
mentioning
confidence: 99%